Pengaruh Experiential Marketing, Perceived Quality, Dan Kualitas Layanan , Terhadap Keputusan Pembelian Konsumen (Studi Kasus Pada Pengguna Aplikasi Maxim Kota Malang) - Ulum, Fahrul; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to analyze the influence of experiential marketing, perceived quality, and service quality on consumer purchasing decisions for Maxim application users in the city of Malang. The research was conducted using a survey method of 90 respondents using purposive sampling. The data analysis method used in this research was quantitative data analysis using multiple linear regression analysis. The data test used is partial hypothesis testing (t test). The research results show that experiential marketing, perceived quality, and service quality have a significant positive effect on consumer purchasing decisions. In conclusion, increasing experiential marketing, perceived quality and service quality can improve consumer purchasing decisions for Maxim application users in the city of Malang. Keywords : Experiential Marketing, Perceived Quality, Service Quality, And Consumer Purchasing Decisions